CONTENT AND SCIENTIFIC-PEDAGOGICAL BASIS OF THE CONCEPT OF COMMUNICATIVE COMPETENCE Teacher at Fergana State University - Evatov Saminjon Sobirovich (Scholar Express Journal, 2022)
There is a growing need to pay special attention to the development of communicative competence and improve educational technology
Keywords: Communicative competence; information and communication tools; psychophysiological features; intellectual and creative development